EFEKTIVITAS ECENG GONDOK (Echhornia crassipes) DALAM PENYERAPAN KADMIUM (Cd) PADA LEACHATE TPA GUNUNG TUGEL - Sri Lestari; Slamet Santoso; Sulastri Anggorowati (Molekul, 2011)
Leachate is liquid of result organic garbage that contain substance is dissolved and suspension as decomposition by microorganism. Leachate contain material organic with high level and many formed at landfill with open dumping system. Material organic in leachate can be reduced by phytoremediation with water hyacinth (Echhorniacrassipes). The aim of research are know large closure of water hyacinth, long residence time and the best interaction to reduce the levels of material organic in leachate. Method of research was designed experimental based on Completely Randomized Design (CRD) with Factorial Design. The first factor are closing large percentage of water hyacinth (0%, 25%, 50%, 75% and 100%) and the second factor are long residence time (4 days, 5 days and 6 days). Result of research showed that is closing large of 75% is the best treatment to reducing level of Cd that is 29,279%. and long residence time of 6 days is the best treatment to reducing level of Cd that is 27,211%. Interaction closing large of 75% and long residence time of 6 days is the best treatment to reducing level of Cd that is 39,770%